Electrical analysis of PVA/PAMPS/CNF polymer blend electrolytic membranes. (2021) - Joshi, Alankrita; Panwar, Varij
Abstract: The electrolytic polymer sensors are of great interest for the scientific communities depending on their properties and applications such as fuel cells, biosensors, electromagnetic shielding. Different organic polymers show different properties and in general are insulators. Various concentrations of different polymers are mixed together and different properties are analysed. In this paper, the electrolytic membranes of Poly-vinyl alcohol (PVA)/ poly(2-acrylamido-2-methyl-1-propanesulfonic acid) (PAMPS)/ CNF(Carbon nanofibres) were developed and the Dielectric constant, Conductivity and Dissipation Factor are evaluated in between the frequency range of 20 Hz to 10 MHz. Pure PVA with 0.6gm PAMPS (PAMPS gives best result for 0.6gm) is taken and different concentrations of CNF are mixed with it. Differences in the properties for the varying concentrations of CNF in the membranes was analysed using the impedance analyser. From the curves obtained for different concentrations it was concluded that the composition having 0.06gm of CNF shows highly effective dielectric properties and the conductivity of the membranes also started decreasing at low frequency and becomes almost stable as the frequency increases.